Self-Interference Suppression Based on Sampled-Data H8 Control for Baseband Signal Subspaces - Hampei Sasahara; Masaaki Nagahara; Kazunori Hayashi; Yutaka Yamamoto (SICE Journal of Control, Measurement, and System Integration, 2019)
In this paper, we propose a design method of self-interference cancelers for in-band full-duplex wireless relaying taking account of baseband signal subspaces. We model the relaying system with self-interference as a sampled-data feedback control system. Then we formulate the design problem as a sampled-data H8 control problem with a generalized sampler and a generalized hold. The problem can be reduced to a discrete-time l2-induced norm optimization problem by explicitly considering the subspace spanned by baseband signals. Moreover, for implementation, we also adopt ideal uniform samplers and zero-order holds with digital filters and up/down samplers. Under these implementation constraints, we reformulate the problem as a standard discrete-time H8 control problem by using the discrete-time lifting technique. Simulation results are shown to illustrate the effectiveness of the proposed method.